Correlating sentinel-2-derived NDVI with the amount of visible color changes and seed fall of Glasswort (Salicornia herbacea L.) during it's ripening stage - Sepehry, Adel; Akay, Abdullah Emin; Nodehi, Negin (Gorgan University of Agricultural Sciences and Natural Resources, 2023)
Glasswort (Salicornia herbacea) is a succulent plant that grows widely around intertidal zone of Gomishan Lagoon in eastern boarders of the Caspian Sea in Iran. Due to its medicinal, industrial, and economic values, tendency of local people to utilize it from natural habitats, and thus its plantation is growing in recent years. One of the challenges to managing a glasswort farm is to know the appropriate date to harvest since glasswort seeds ripe quickly and seedfall happens considerably by little shake. An effective way of defining appropriate harvesting dates should be correlated mostly with visual characteristics of the plant; like its color change. If NDVI values derived from remote sensing imageries show a meaningful correlation with the amount of visible greenness of the plant, and its ripening stage, then the qualitative estimation of the color of the field can be substituted with the quantitative estimating the amount of filed reflectance and consequently defining appropriate harvesting time of the plant. Experimental research was therefore conducted to answer this problem by relating the changes in Glasswort color classes and its amount of seedfall to the amount of Normalized Difference Vegetation Index (NDVI) values that were obtained from SENTINEL 2 remotely sensed imagery. Field sampling was started from 2019.11.8 to 2019.12.21. The proportion of greenness, redness and brownness of the plants within each sample plots were estimated. The amount of falling seeds were also collected and weighed within each sample plots. The maximum NDVI values of 41 Sentinel-2 images during 2018-2020 within Glasswort phenological period were extracted and were correlated with the color class of the plant and the weight of seedfall in sample plots. Results showed a strong correlation between NDVI and brownness color class (R2 =0.80) and a strong negative correlation with amount of seedfall of the plant (R2 =-0.83). When the brownness color class of the Glasswort filed exceeds 50 percent, the seeds have reached to their highest maturity and are ready to be harvested. This strong but negative correlation between maximum NDVI values and Glasswort seedfall supports the findings of the correlation of the filed data. Our findings therefore can help filed workers to have an observable phenomenon of the plant to decide when to start harvesting Glasswort in the study area. © The Author(s).
Keywords: Gomishan Lagoon; Halophyte plantation; Harvesting dates; Normalized Difference; Saline agriculture; Seedfall; Vegetation Index